Patterned payments: explaining victim group variation in West German reparations policy - Greenstein, Claire (International journal of transitional justice, 2020)
Why, once governments decide to pay reparations, do they fulfill their reparations promises to some groups and not to others? I argue that the organizational capacity of a victim group helps explain which groups receive reparations. I develop this argument through an in-depth case study of the postwar experience of German Sinti and Roma, supported by archival and interview data. I show that organized victim groups received reparations from the West German government in the 1950s, while Romani Germans, who did not organize until the late 1970s, were largely and deliberately excluded from receiving reparations payments until 1981, when the West German government created a reparations fund to benefit Romani German survivors. I show that this policy change cannot be understood without considering the efforts of Romani organizations.